Effect of Gastric Acid on the Surface Properties of Different Composite Resin Restorative Materials: Scanning Electron Microscope (SEM) Evaluation - Cemile Kedici Alp; Cansu Dağdelen Ahısha (Current Research in Dental Sciences)
Objective: The aim of this study was to evaluate the effect of gastric acid on different resin-based composites with surface microhardness, surface roughness and scanning electron microscopy (SEM).Methods: Three different composite resin restorative materials (Clearfil Majesty ES-2{Kuraray, Tokyo, Japan}, Beautifil II {Shofu, Ratingen, Germany}, Group Beautifil II LS {Shofu, Ratingen, Germany}) were used. Vickers microhardness and surface roughness measurements were evaluated at baseline, after 7 and 14 days of soaking in gastric acid. SEM images were obtained to examine the effects of gastric acid on the surface properties of the composites.Results: When the difference in the microhardness values of the composite resins was compared, the time-dependent change in all composites was found to be statistically significant. The most surface roughness and hardness changes occurred in Beautifil II group (P:0.000; P<.05). According to SEM images, Beautifil II group was most affected by gastric acid, while Clearfil Majesty group was least affected.Conclusion: In vitro conditions gastric acid increased the surface roughness of different composites while decreasing their microhardness. As a result, if these restorative materials are to be preferred in patients with reflux, they should be checked frequently. In the presence of an uncontrollable situation, the use of these restorative materials can be limited.Keywords: Gastric acid, microhardness, surface roughness, SEM